Prevention of Influenza A(H7N9) and Bacterial Infections in Mice Using Intranasal Immunization With Live Influenza Vaccine and the Group B Streptococcus Recombinant Polypeptides. Issue 1 (1st June 2017) - Desheva, Yulia A; Leontieva, Galina F; Kramskaya, Tatiana A; Smolonogina, Tatiana A; Grabovskaya, Kornelia B; Landgraf, Galina O; Karev, Vadim E; Suvorov, Alexander N; Rudenko, Larisa G
We investigate the protective effect of combined vaccination based on live attenuated influenza vaccine (LAIV) and group B streptococcus (GBS) recombinant polypeptides against potential pandemic H7N9 influenza infection followed by GBS burden. Mice were intranasally immunized using 10 7 50% egg infectious dose (EID50 ) of H7N3 LAIV, the mix of the 4 GBS peptides (group B streptococcus vaccine [GBSV]), or combined LAIV + GBSV vaccine. The LAIV raised serum hemagglutination-inhibition antibodies against H7N9 in higher titers than against H7N3. Combined vaccination provided advantageous protection against infections with A/Shanghai/2/2013(H7N9)CDC-RG influenza and serotype II GBS. Combined vaccine significantly improved bacterial clearance from the lungs after infection compared with other vaccine groups. The smallest lung lesions due to combined LAIV + GBSV vaccination were associated with a prevalence of lung interferon-γ messenger RNA expression. Thus, combined viral and bacterial intranasal immunization using H7N3 LAIV and recombinant bacterial polypeptides induced balanced adaptive immune response, providing protection against potential pandemic influenza H7N9 and bacterial complications.